2019
DOI: 10.3897/phytokeys.121.29924
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of rheophytes of Cameroon

Abstract: Rivers in Cameroon were surveyed to collect and document rheophytic plants. Rheophytes are the dominant aquatic macrophytes in tropical river systems, where they are adapted to extreme environments of rushing water (e.g., river rapids, waterfalls and flash floods). Rheophytic plants are useful indicators of river health. However, their habitats are threatened by human activities such as agriculture, plantation development, alluvial mining and dam construction, particularly in tropical countries. In this survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…More recently intensive surveys dedicated to finding sites for this family in Cameroon have been carried out above all by Ghogue, but also by dedicated Podostemaceae researchers from Switzerland, Ghana, USA, Japan and Britain but no further locations for Saxicolella nana have come to light. Kuetegue et al (2019) studying the rheophytes of Cameroon concluded that it should be assessed as Endangered ENB2ab (ii, iii), with no additional data. Much of the length of the Nyong S of Yaoundé is not suitable for Podostemaceae due to the absence of rapids.…”
Section: Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently intensive surveys dedicated to finding sites for this family in Cameroon have been carried out above all by Ghogue, but also by dedicated Podostemaceae researchers from Switzerland, Ghana, USA, Japan and Britain but no further locations for Saxicolella nana have come to light. Kuetegue et al (2019) studying the rheophytes of Cameroon concluded that it should be assessed as Endangered ENB2ab (ii, iii), with no additional data. Much of the length of the Nyong S of Yaoundé is not suitable for Podostemaceae due to the absence of rapids.…”
Section: Recognitionmentioning
confidence: 99%
“…The Red Data Book of Cameroon Plants (Onana & Cheek 2011: 253) reassess the species as EN B2ab(iii) since two locations (above) are recorded. Kuetegue et al (2019) Taylor (1953: 57) stated: "Amongst African genera the plant is most closely related to Saxicolella and Pohliella, in each of which the flowers is unistaminate and erect within the spathella, but it differs from these genera in having entire rosulate leaves, much more shortly pedicellate flowers and complanate stigmas". At that time both genera were only known from their type species and their circumscription was incompletely known.…”
Section: Distribution Gabon Ogoouémentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic macrophytes include both vascular and non-vascular plants which could be floating, submerged or emerged in shallow waters and influence the physical, chemical and biological environment [5]. Macrophytes generally colonize shallow ecosystems such as streams, rivers, lakes, ponds, marine environments, and even rapids and falls as in the case of Podostemaceae [6] and constitute important ecological engineers which influence ecological processes (e.g., nutrient cycling, habitat, and food provision to fishes and zooplankton, water purification and ecological attributes of other biotic aquatic attached assemblages like species diversity and composition). Owing to their high rate of biomass production, macrophytes have primarily been characterized as an important food resource for aquatic organisms, providing both living (grazing food webs) and dead organic matter (detritivorous food webs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…A hand full of studies have been documented on aquatic macrophytes in Cameroon, ranging from the identification of endemic aquatic taxa like Podostemaceae in rivers and rapids in the different regions of Cameroon [6], the role of aquatic plants in nutrient and heavy metallic uptake in both lotic and lentic ecosystems [14] [15] and their role in phytoremediation [16] [17] [18].…”
Section: Introductionmentioning
confidence: 99%